2012
DOI: 10.1056/nejmoa1114540
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of PCI at Hospitals with or without On-Site Cardiac Surgery

Abstract: We found that PCI performed at hospitals without on-site cardiac surgery was noninferior to PCI performed at hospitals with on-site cardiac surgery with respect to mortality at 6 weeks and major adverse cardiac events at 9 months. (Funded by the Cardiovascular Patient Outcomes Research Team [C-PORT] participating sites; ClinicalTrials.gov number, NCT00549796.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 23 publications
8
73
0
3
Order By: Relevance
“…Less experienced operators should have additional oversight, such as backup support. The CPORT-E Trial serves as a model for facilities performing PCI without on-site cardiac surgery [8]. Consistent with its design, such facilities should participate in national registries, routinely utilize riskadjustment tools, have immediately available consultation with a tertiary care center, implement crosstraining of personnel, and have a well-developed system for expeditious transfer for emergency coronary artery bypass graft (CABG).…”
Section: Institutional and Operator Qualifications And Components Of mentioning
confidence: 99%
“…Less experienced operators should have additional oversight, such as backup support. The CPORT-E Trial serves as a model for facilities performing PCI without on-site cardiac surgery [8]. Consistent with its design, such facilities should participate in national registries, routinely utilize riskadjustment tools, have immediately available consultation with a tertiary care center, implement crosstraining of personnel, and have a well-developed system for expeditious transfer for emergency coronary artery bypass graft (CABG).…”
Section: Institutional and Operator Qualifications And Components Of mentioning
confidence: 99%
“…In 1 meta-analysis, after adjusting for publication bias, the mortality rate for nonprimary PCI was 25% higher at centers without on-site surgery compared with centers that had on-site surgery (OR, 1.25; 95% CI, 1.01-1.53; P ¼ 0.04) [20]. However, it is important to note that these meta-analyses preceded the publication of the 2 randomized trials [9,11]. Therefore, based on these [2,24,25].…”
Section: Recent Literature On Pci Without On-site Surgerymentioning
confidence: 99%
“…Since 2006, 11 original studies and 3 meta-analyses on the topic of PCI without on-site surgery have been identified by a computerized systematic literature search using Medline (PubMed and Ovid) and Cochrane Databases [9,[11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Recent Literature On Pci Without On-site Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, this proliferation has been aided, in part, by data suggesting that PCI can be performed safely without on-site cardiac surgery. 9,10 Given the aforementioned association between PCI volume and outcomes, the net effect of any such growth is likely to represent a complex balance between improved access and decreasing procedural volumes (both for hospitals and operators).…”
Section: Circulationmentioning
confidence: 99%